Carcinosarcoma (Metaplastic Carcinoma) breast: A rare and aggressive primary – report of two cases with review of literature - Gunjesh Kumar Singh; Pragya Singh; K T Bhowmik (Indian Journal of Medical and Paediatric Oncology)
Carcinosarcoma (CS) also known as metaplastic carcinoma of the breast is a rare and aggressive type of malignancy with controversial origin. Currently, there are no standard treatment guidelines outlined, owing to the rarity of the disease, but according to the available literature, surgery followed by adjuvant radiation therapy has the greatest benefit. We are presenting two cases of CS of breast developing metastasis. One of the cases presented with lung metastasis during the course of follow-up and responded significantly to chemotherapy, and the other is currently receiving chemotherapy. The cases are being presented here along with the literature review enlightening the current knowledge and available treatment options.